Photoproduction of π0ω off protons for Eγ≤3 GeV - Flemming, H.; Messchendorp, J. G.; Menze, D.; Matthäy, H.; Funke, Chr.; Thoma, U.; Suft, Gabriele; Radkov, A.; Fösel, Angela; Schoch, B.; Schmidt, C.; Walther, D.; et al. (European Physical Journal A, 2007)
Differential and total cross-sections for photoproduction of γp→pπ0ω and γp→Δ+ω were determined from measurements of the CB-ELSA experiment, performed at the electron accelerator ELSA in Bonn. The measurements covered the photon energy range from the production threshold up to 3GeV.